Une analyse économique des loteries québécoises - Boucher, Michel (L'Actualité économique, 1974)
AbstractThe focus of this article is to analyse the reasons for the success of the Québec Lotteries. To do it perfectly, we study the technical terms of the lottery, drawing, namely the expected value, the probability of winning a prize and the inequality of the prize distribution. Then we analyse some changes introduced by Loto-Québec and we contrast the results with other more established lotteries and the differences so observed may provide additional reasons for its success.In the second part, we use the theory of choice involving risk as described by Allais and Tobin to explain the demand for lotteries tickets. We find, by a statistical analysis, where the independent variables are the mean value and the variance of the prize distribution, that people who buy tickets are generally speaking risk-averters and not risk-lovers and they behave as such when Loto-Québec changes the mean value and the variance.